Carbon Nanotubes-Filled Siloxane Composite Foams for Oil Recovery Application: Compression Properties - Elpida Piperopoulos (Fibers, 2020)
This paper studies the correlation between oil recovery usability and mechanical behavior under compression loads of an innovative oil recovery material. The examined composites are silicone foams filled with carbon nanotubes (CNT). Here, the reutilization of oil recovery processes of the newly developed composite foams is evaluated. In this regard, static and cyclic compressive tests are carried out. Samples filled with pristine and functionalized CNT are tested to evaluate the influence of the filler’s characteristics on the composite foam’s mechanical behavior. The results show that the presence of CNT (CNT-0) increases the elastic modulus (0.030 MPa) and collapse stress (0.010 MPa) of the siloxane matrix. On the contrary, as the CNT functionalization degree increases, a worsening of the composite’s mechanical performance is observed. CNT-0 foam evidences, also, the optimal mechanical stability to cyclic compressive loads, maintaining high stress values until 30 cycles. Furthermore, a correlation between the absorption capacity, elastic modulus, and cyclability is reported, highlighting a simplified approach to tailor the high absorption durability performance of filled CNT silicone foams. The promising results confirm the possible reuse of these new composite foams as absorbent materials for oil spill recovery applications.